Analysis of the Needs for Civics and Social Sciences Learning Design Based on Technology, Information, and Communication - Vachry Dhani; Yeni Erita; Novalina INDRIYANIc; Wiwit SANJAYA (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2023)
Learning design is the design of a lesson that will be used in learning as a teacher's guide. With more and more teacher knowledge about how to design learning, it will also have a good impact on the learning that is carried out. There are still many teachers who have not designed learning properly to stimulate students. Especially now that the world of education has developed in line with technological developments. Of course, there are many choices for teachers in designing learning by integrating learning with technology. This study aims to determine the needs of Civics and Social Sciences learning designs based on technology, information, and communication. Writing this article using qualitative research with a descriptive approach. Data collection was carried out by means of a literature study. The results of the analysis of various journals and books found show the need for creative Civics and Social Studies learning designs and a positive influence on the use of ICT in learning as well as helping the teacher's task in learning.